-6y=-4y-18

Simple and best practice solution for -6y=-4y-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y=-4y-18 equation:



-6y=-4y-18
We move all terms to the left:
-6y-(-4y-18)=0
We get rid of parentheses
-6y+4y+18=0
We add all the numbers together, and all the variables
-2y+18=0
We move all terms containing y to the left, all other terms to the right
-2y=-18
y=-18/-2
y=+9

See similar equations:

| 6(b-10)=8(6+8) | | 4x+7=75-8 | | 2^(x)=32000 | | 3(1-4p)=30-3p | | 8n-6=250 | | 5(3m-8)=38+2m | | 8p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p+14=5p+278p | | 28=-5(u+1)-2 | | -5v-9(v+6)=-96 | | 21-2w=13 | | 16+6s+9s=16 | | 63=-9a+3(a+3) | | 5(5-2x)=115 | | -8=-v+12/3 | | 3x+3=3x+7 | | 3x+3=-5x-3 | | -70=-4x-3x | | 6(t+1)=84 | | -61=-6(z+7)-13 | | 6x+19=5x-4 | | 31=-9(7+w)-5 | | -2(r-4)=-7-7r | | 6c+6=3c−6 | | -23=2x-1 | | -6(3+s)=-42 | | 10w+5=11w-3 | | -w/2+19=15 | | 20=17+q/3 | | 6+x=5x-9 | | -3x+7=7(1+8x) | | 3(d-6)-7=19 | | -7.6-15.1f=16.98-12f+12.93 |

Equations solver categories